2012
DOI: 10.1080/10810730.2012.665426
|View full text |Cite
|
Sign up to set email alerts
|

Conversation and Compliance: Role of Interpersonal Discussion and Social Norms in Public Communication Campaigns

Abstract: This study explores the role of interpersonal discussion and social norms in a public health campaign, the BBC Condom Normalization Campaign, designed to promote conversation and change the public perception of condom use in India. Drawing upon the integrative model of behavioral prediction, attitudes, self-efficacy, subjective norms, and descriptive norms were predicted to relate to behavioral intentions to use condoms. It is important to note that the valence of discussion was hypothesized to relate to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…For example, in the context of HPV vaccination, conversations that were favorable (i.e., supported the vaccine) were linked to health-promotive norms and attitudes as well as intentions to receive the HPV vaccine (Dunlop et al, 2010). In the context of condom use in South India, positive campaign-prompted conversations were shown to predict greater health-promotive attitudes, higher self-efficacy for condom use, and subjective and descriptive norms supporting condom use (Frank et al, 2012). A study of binge drinking in the Netherlands found that negative conversational valence about alcohol was linked to greater intention to refrain from binge drinking (Hendriks et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the context of HPV vaccination, conversations that were favorable (i.e., supported the vaccine) were linked to health-promotive norms and attitudes as well as intentions to receive the HPV vaccine (Dunlop et al, 2010). In the context of condom use in South India, positive campaign-prompted conversations were shown to predict greater health-promotive attitudes, higher self-efficacy for condom use, and subjective and descriptive norms supporting condom use (Frank et al, 2012). A study of binge drinking in the Netherlands found that negative conversational valence about alcohol was linked to greater intention to refrain from binge drinking (Hendriks et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to radio programming, the project engages and mobilizes community members within radio-listening groups to promote discussion, reflection, and critical thinking around radio-broadcasted messages to facilitate behaviour change [3133]. In the Change project, sex-separate LDGs will meet to dialogue about the radio programming and to create “homogenous, tightly knit groups in which there is private dissent against the current norm” [13] and support for the members’ integration of messages into everyday life [34].…”
Section: Methodsmentioning
confidence: 99%
“…One powerful effect of EE is that it sparks dialogue about critical social issues among audiences (Chatterjee, Bhanot & Frank et al 2009;Frank, Chatterjee & Chaudhuri et al 2012;Papa & Singhal 2010;Rogers, Vaughan & Swalehe et al 1999;Singhal & Rogers 2002;Usdin et al 2004;Valente, Kim & Lettenmaier et al 1994). Such dialogue not only reinforces key campaign messages, but can also bring previously invisible issues into focus in the public consciousness, encouraging them to be interrogated or re-examined.…”
Section: Challenging Redefining and Re-imagining Masculinitiesmentioning
confidence: 97%